The challenges of meeting the blood transfusion requirements in Sub-Saharan Africa: the need for the development of alternatives to allogenic blood - Osaro, Erhabor (Dove Medical Press, 2011)
As a resource, allogenic blood has never been more in demand than it is today. Escalating elective surgery, shortages arising from a fall in supply, a lack of national blood transfusion services, policies, appropriate infrastructure, trained personnel, and financial resources to support the running of a voluntary nonremunerated donor transfusion service, and old and emerging threats of transfusion-transmitted infection, have all conspired to ensure that allogenic blood remains very much a vital but limited asset to healthcare delivery particularly in Sub-Saharan Africa. This is further aggravated by the predominance of family replacement and commercially remunerated blood donors, rather than regular benevolent, nonremunerated donors who give blood out of altruism. The demand for blood transfusion is high in Sub-Saharan Africa because of the high prevalence of anemia especially due to malaria and pregnancy-related complications. All stakeholders in blood transfusion have a significant challenge to apply the best available evidenced-based medical practices to the world-class management of this precious product in a bid to using blood more appropriately. Physicians in Sub-Saharan Africa must always keep in mind that the first and foremost strategy to avoid transfusion of allogenic blood is their thorough understanding of the pathophysiologic mechanisms involved in anemia and coagulopathy, and their thoughtful adherence to the evidenced-based good practices used in the developed world in a bid to potentially reduce the likelihood of allogenic blood transfusion in many patient groups. There is an urgent need to develop innovative ways to recruit and retain voluntary low-risk blood donors. Concerns about adverse effects of allogenic blood transfusion should prompt a review of transfusion practices and justify the need to search for transfusion alternatives to decrease or avoid the use of allogenic blood. These strategies should include the correction of anemia using pharmacological measures (use of antifibrinolytics to prevent bleeding and the use of erythropoietin and oral and intravenous iron to treat anemia) use of nonpharmacologic measures (preoperative autologous blood transfusion, perioperative red blood cell salvage and normothermia to reduce blood loss in surgical patients). All these strategies will help optimize the use of the limited blood stocks.